Pengaruh Kecepatan Pengadukan Dan Tekanan Pemompaan Pada Kombinasi Proses Koagulasi Dan Membran Ultrafiltrasi Dalam Pengolahan Limbah Cair Industri Karet - Selvi ' Angraini; Jhon Armedi Pinem; Edy ' Saputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Laboratory scale studies have been conducted to assess the effect of stirring speed and pressure pumping on a combination of coagulation and ultrafiltration membranes in crumb rubber wastewater treatment. Prior to treatment, neutralization of wastewater in advance using 0.1 N NaOH to obtain a pH neutral in wastewater. The function of neutralization is to optimize the performance of the coagulation process. wastewater which has been neutralized then carried coagulation-flocculation process using a coagulant PAC with a concentration of 100 ppm. Coagulation process is done by varying the stirring speed of 100 rpm, 200 rpm and 300 rpm for 5 minutes and continued with the process of flocculation with a stirring speed of 60 rpm for 10 minutes. Wastewater then allowed to sedimentation for 30 minutes to precipitate the floc-floc had formed. Then the wastewater is separated from the sediment / floc using filter paper. The result showed that the maximum stirring speed in the coagulation process to reduce pollutant load in wastewater rubber is 200 rpm. Wastewater has been coagulated with stirring speed of 200 rpm and then fed into the ultrafiltration membranes with a variation of pressure of 1 bar, 2 bar and 3 bar. The maximum operating pressure ultrafiltration membranes to reduce the pollutant load in wastewater rubber is 3 bar. A combination of coagulation and ultrafiltration membrane able to reduce pollutant load in wastewater rubber with a value of BOD decline is 84.11%, COD is 84.17% , TSS is 95.40% and ammonia is 51.19%.Keywords: Ammonia, BOD, COD, coagulation, wastewater,ultrafiltration membranes, PAC, TSS.